Pengaruh Bimbingan Konseling (BK) terhadap Kemampuan Belajar Siswa Introvert - Ardiansyah, Yusuf; Cahyningrum, Yuniana (Pendagogia: Jurnal Pendidikan Dasar, 2023)
Counseling guidance helps students gain independence in self-understanding, so that students can orient themselves to existing needs. This lack of self-confidence in students hinders the development of intellectual achievement, skills and independence and hinders students from interacting directly with the community. Research using qualitative research methods study literature. In this service, the counselor controls every step of the consultation process so that it can run effectively. And with this activity, students can express their problems. themselves, so that students can orient themselves to existing needs. This lack of self-confidence in students hinders the development of intellectual achievement, skills and independence and hinders students from interacting directly with the community.